2009
DOI: 10.1007/s12594-009-0187-5
|View full text |Cite
|
Sign up to set email alerts
|

Joints as fingerprints of stress in the quaternary carbonate deposits along coastal Saurashtra, Western India

Abstract: Coastal cliffs and shore platforms are important geomorphic features of coastal areas of Saurashtra. These features are composed of medium to coarse grained carbonate sand and are designated as "Miliolitic limestones" that range in age from Middle to Late Pleistocene. Significant jointing has been observed in the Middle Pleistocene Miliolite Formation as well as in the younger shell limestone that comprises Chaya Formation of Late Pleistocene. Along with NE-SW trend which is the direction of maximum horizontal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…Nott's (2003) equation for joint bounded boulder scenario (JBBS) assumed that boulder before being detached had only one side exposed to wave and is limited by five sides. As the regional setting shows shore platform and the cliff sections are jointed (Bhonde and Bhatt, 2009), the JBBS fits very well in present case (Fig. 2b).…”
Section: Methodssupporting
confidence: 75%
See 1 more Smart Citation
“…Nott's (2003) equation for joint bounded boulder scenario (JBBS) assumed that boulder before being detached had only one side exposed to wave and is limited by five sides. As the regional setting shows shore platform and the cliff sections are jointed (Bhonde and Bhatt, 2009), the JBBS fits very well in present case (Fig. 2b).…”
Section: Methodssupporting
confidence: 75%
“…saltation, rolling, suspension and a combination of these. The study area shows pronounce joints (Bhonde and Bhatt, 2009) based on which we assumed that the boulders were joint bounded; the tabular morphology of boulders and boring marks indicate it being derived from shore platform. Also NV-3 was found inverted at a distance of about 36 m from high tide line.…”
Section: Implications Of Deviation From Modeled Resultsmentioning
confidence: 99%
“…Diu is just north of the NE–SW Narmada Son Fault; this fault lies offshore and south of some onland faults, namely the Chachhar and Rupen faults (Bhatt et al., ). Recently, a few faults have been mapped on land (Gandhi et al., ), along with conspicuous joint sets in the late Quaternary limestone, and these manifest the effects of stress (Bhonde & Bhatt, ).…”
Section: Study Areamentioning
confidence: 99%
“…The Saurashtra peninsula has experienced pronounced neotectonic activity as suggested by seismicity 21,22 , preserved raised marine notches 11,12 , development of joints 23 and archeological evidences 24 . Sharma et al 1 reported that fluvially reworked miliolites were deposited during the period 17-75 ka.…”
mentioning
confidence: 99%